Anti-TNF-α Monoclonal Antibody Therapy Improves Anemia through Downregulating Hepatocyte Hepcidin Expression in Inflammatory Bowel Disease - Shu, Weigang; Pang, Zhi; Xu, Chunjin; Lin, Jian; Li, Gengfeng; Wu, Wei; Sun, Suofeng; Li, Junxiang; Li, Xiuling; Liu, Zhanju (Mediators of Inflammation, 2019)
Anemia is one of the most common complications in patients with inflammatory bowel disease (IBD). Hepcidin as a key regulator of iron metabolism is pivotal in mediating the occurrence of anemia of chronic disease. Herein, we analyzed the levels of hepcidin in sera from IBD patients by enzyme-linked immunosorbent assay and investigated its potential role in regulating the anemia in IBD. We observed that the levels of serum hepcidin were increased in active IBD patients compared with those in remitted IBD patients and healthy controls and that serum hepcidin was associated with disease activity, CRP, and ESR, respectively. Importantly, we found that the increased levels of serum hepcidin were positively correlated with the severity of anemia and the imbalance of iron metabolism in anemic UC and CD patients. Proinflammatory factors (e.g., IL-6, IL-17, and TNF-α) were positively correlated with the concentrations of serum hepcidin in IBD patients. Interestingly, hepcidin was found to be decreased in patients with Crohn’s disease after successful therapy with anti-TNF-α mAb (i.e., infliximab), indicating the underlying association between TNF-α and hepcidin expression. To investigate the specific mechanisms involved, we cultured LO2 and HepG2 cell lines in vitro under stimulation with TNF-α and observed that the levels of hepcidin mRNA were markedly upregulated in caspase-3/8- and NF-κB-dependent manners. Therefore, our data suggest that TNF-α stimulates the expression of hepcidin in IBD patients, resulting in aggravated anemia and that blockage of TNF-α or the caspase-3/8 and NF-κB pathways could downregulate hepcidin expression. This study provides inspiration for the therapy and management of anemia in IBD.